2020
DOI: 10.1002/lary.28639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Paranasal Sinus Surgery in Granulomatosis With Polyangiitis: A Longitudinal Computed Tomography Study

Abstract: Objectives/Hypothesis Severe chronic rhinosinusitis (CRS) in patients with granulomatosis with polyangiitis (GPA) failing medical therapies can be treated with paranasal sinus surgery. Whether this surgery protects from progressive sinonasal damage remains unknown. Here, we aimed to analyze time‐dependent relations between sinus surgeries and computed tomography (CT) imaging features in the CRS of GPA. Study Design Longitudinal observational study. Methods We assessed CRS features including bone thickening by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…We have previously shown that sinus surgery associates with osteitis development in GPA (13). Consistently, we found a large difference in osteitis outcome between GPA patients with or without a history of sinus surgery (Figure 3).…”
Section: Baseline Clinical and Radiological Features As Risk Factors supporting
confidence: 88%
See 2 more Smart Citations
“…We have previously shown that sinus surgery associates with osteitis development in GPA (13). Consistently, we found a large difference in osteitis outcome between GPA patients with or without a history of sinus surgery (Figure 3).…”
Section: Baseline Clinical and Radiological Features As Risk Factors supporting
confidence: 88%
“…We have described details on the GPA patient cohort in previous paranasal CT studies [12,13]. Briefly, the cohort included all the GPA patients from the Norwegian systemic vasculitis and connective tissue disease registry (NOSVAR), a consentbased patient registry run by the Department of Rheumatology at Oslo University Hospital, who met the following pre-specified inclusion criteria: (I) clinical ANCA vasculitis classifiable as GPA according to the European Medicines Agency (EMA) algorithm [14], (II) at least two sets of archived sinus CT scans available for analysis, with minimum one year between time of baseline CT and time of last CT.…”
Section: Gpa Patient Cohort and Study Timelinementioning
confidence: 99%
See 1 more Smart Citation
“…We have described details on the GPA patient cohort in previous paranasal CT studies [12,13]. Briefly, the cohort included all the GPA patients from the Norwegian systemic vasculitis and connective tissue disease registry (NOSVAR), a consentbased patient registry run by the Department of Rheumatology at Oslo University Hospital.…”
Section: Gpa Patient Cohort and Study Timelinementioning
confidence: 99%
“…Recently, we developed and applied methods suitable for evaluation of serial paranasal sinus CT scans of GPA patients. We used these methods to assess time-dependent CRS changes, with thickening of the bones of the sinus walls as the main marker for sinus damage [12,13].…”
Section: Introductionmentioning
confidence: 99%